Changes to virus taxonomy, the international code of virus classification and nomenclature, and the ICTV statutes ratified by the International Committee on Taxonomy of Viruses (2025) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Juliana Freitas-Astúa; R. Curtis Hendrickson; Holly R. Hughes; Mart Krupovic; et al. (Archives of Virology, 2026)
The 56th meeting of the Executive Committee (EC) of the International Committee on Taxonomy of Viruses (ICTV) was held in Bari, Italy, in July/August, 2024, and 115 submitted taxonomy proposals were reviewed. A total of 112 were subsequently ratified by the ICTV membership. An additional 9 error correction proposals were also approved in August 2025. This article lists the taxonomy proposals that have now been incorporated into release 40 version v2 of the Master Species List ( https://ictv.global/msl ), the Virus Metadata Resource ( https://ictv.global/vmr ), and associated ICTV databases. In addition to the assignments of 1,563 new virus species, 243genera, 55 families, 11 orders, and 8 classes, there were substantial additions to higher taxonomic ranks. These include the creation of a new realm ( Singelaviria ), which is based on the recognition of a separate evolutionary origin for the hallmark capsid genes of members of the kingdom Helvetiavirae. These express capsid proteins forming a single jelly-roll fold that is structurally and evolutionarily distinct from those of members of the family Bamfordvirae , assigned to the realm Varidnaviria . Furthermore, the realm Varidnaviria underwent a major reorganization, including the addition of a new kingdom, Abadenavirae . Another notable change was the classification of the vertebrate-infecting single-stranded DNA anellovirids into a new phylum Commensaviricota (kingdom Shotokuvirae , realm Monodnaviria ). Archaeal viruses infecting the hyperthermophilic Archaeoglobi were assigned to a new phylum Calorviricota , in the kingdom Trapavirae (realm Monodnaviria ), whereas RNA viruses infecting hyperthermophilic bacteria were classified into a new phylum Artimaviricota (realm Riboviria ). In recognition of his extensive and valuable contributions to virus taxonomic developments in Study Groups and over the period of his EC membership, Stuart Siddell was honoured as a new life member of the ICTV. The ICTV has created a new strategy for disseminating information on taxonomy advances through annual open-access publication of citeable taxonomy proposal summaries from each ICTV Subcommittee. A collective total of 354 co-authors of the seven summaries were drawn from members of each Subcommittee, the EC, and a very large number of contributors from the wider virology community.

Personalized Environmental Control Systems (PECS): Systematic review of benefits for thermal comfort, air quality, health, and human performance - Dolaana Khovalyg; Mariya P. Bivolarova; Jun Shinoda; Douaa Al-Assaad; Marika Vellei; Karol Bandurski; Giorgia Chinazzo; Ongun B. Kazanci; Joyce Kim; Tobias Kramer; Aleksandra Lipczynska; Shichao Liu; et al. (Building and Environment, 2025)

Out of habitat marine mammals – Identification, causes, and management recommendations - Laetitia Nunny; Mike Bossley; Rebecca M. Boys; Philippa Brakes; Tilen Genov; E.C.M. Parsons; Katharina J. Peters; Naomi A. Rose; Claire A. Simeone; Karen A. Stockin; Courtney S. Vail; Krista van der Linde; et al. (Marine Policy, 2025)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

Ozone at Mace Head, Ireland from 1987 to 2021: Declining baselines, phase-out of European regional pollution, COVID-19 impacts - Richard G. Derwent; David D. Parrish; Alistair J. Manning; T. Gerard Spain; Peter G. Simmonds; Simon O'Doherty (Atmospheric Environment, 2024)

Genetic diversity of RNA viruses infecting invertebrate pests of rice - Haoran Wang; Shufen Chao; Qing Yan; Shu Zhang; Guoqing Chen; Chonghui Mao; Yang Hu; Fengquan Yu; Shuo Wang; Liang Lv; Baojun Yang; Jiachun He; et al. (Science China Life Sciences, 2024)

High-frequency, continuous hydrogen observations at Mace Head, Ireland from 1994 to 2022: Baselines, pollution events and ‘missing’ sources - Richard G. Derwent; Peter G. Simmonds; Simon O'Doherty; Alistair J. Manning; T. Gerard Spain (Atmospheric Environment, 2023)

Correction to: Changes to virus taxonomy and the ICTV Statutes ratifed by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Renaming of the genus Flavivirus to Orthoflavivirus and extension of binomial species names within the family Flaviviridae - Thomas S. Postler; Martin Beer; Bradley J. Blitvich; Jens Bukh; Xavier de Lamballerie; J. Felix Drexler; Allison Imrie; Amit Kapoor; Galina G. Karganova; Philippe Lemey; Volker Lohmann; Peter Simmonds; et al. (Archives of Virology, 2023)

Seasonal dynamics of the wild rodent faecal virome - Jayna Raghwani; Christina L. Faust; Sarah François; Dung Nguyen; Kirsty Marsh; Aura Raulo; Sarah C. Hill; Kris V. Parag; Peter Simmonds; Sarah C. L. Knowles; Oliver G. Pybus (Molecular Ecology, 2023)
Viral discovery studies in wild animals often rely on cross‐sectional surveys at a single time point. As a result, our understanding of the temporal stability of wild animal viromes remains poorly resolved. While studies of single host–virus systems indicate that host and environmental factors influence seasonal virus transmission dynamics, comparable insights for whole viral communities in multiple hosts are lacking. Utilizing noninvasive faecal samples from a long‐term wild rodent study, we characterized viral communities of three common European rodent species ( Apodemus sylvaticus , A. flavicollis and Myodes glareolus ) living in temperate woodland over a single year. Our findings indicate that a substantial fraction of the rodent virome is seasonally transient and associated with vertebrate or bacteria hosts. Further analyses of one of the most common virus families, Picornaviridae, show pronounced temporal changes in viral richness and evenness, which were associated with concurrent and up to ~3‐month lags in host density, ambient temperature, rainfall and humidity, suggesting complex feedbacks from the host and environmental factors on virus transmission and shedding in seasonal habitats. Overall, this study emphasizes the importance of understanding the seasonal dynamics of wild animal viromes in order to better predict and mitigate zoonotic risks.

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2022)

Differentiating between viruses and virus species by writing their names correctly - Francisco Murilo Zerbini; Stuart G. Siddell; Arcady R. Mushegian; Peter J. Walker; Elliot J. Lefkowitz; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Bas E. Dutilh; María Laura García; Sandra Junglen; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A proposed division of the family Picornaviridae into subfamilies based on phylogenetic relationships and functional genomic organization - Roland Zell; Nick J. Knowles; Peter Simmonds (Archives of Virology, 2021)
The highly diverse virus family Picornaviridae presently comprises 68 approved genera with 158 species plus many unassigned viruses. In order to better match picornavirus taxonomy to the functional and genomic groupings between genera, the establishment of five subfamilies ( Caphthovirinae, Kodimesavirinae, Ensavirinae, Paavivirinae and Heptrevirinae ) is proposed. The subfamilies are defined by phylogenetic analyses of 3CD (precursor of virus-encoded proteinase and polymerase) and P1 (capsid protein precursor) coding sequences and comprise between 7 and 22 currently approved virus genera. Due to the high within-subfamily and between-subfamily divergences of the picornavirus genera, p-distance estimates are unsuited for the demarcation of subfamilies. Members of the proposed subfamilies typically show some commonalities in their genome organisations, including VP1/2A cleavage mechanisms and possession of leader proteins. Other features, such as internal ribosomal entry site types, are more variable within and between members of genera. Some subfamilies are characterised by homology of proteins 1A, 2A, 2B and 3A encoded by members, which do not belong to the canon of orthologous picornavirus proteins. The proposed addition of a subfamily layer to the taxonomy of picornaviruses provides a valuable additional organisational level to the family that acknowledges the existence of higher-level evolutionary groupings of its component genera.

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Changes to virus taxonomy and the Statutes ratified by the International Committee on Taxonomy of Viruses (2020) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Donald M. Dempsey; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; R. Curtis Hendrickson; Sandra Junglen; Nick J. Knowles; et al. (Archives of Virology, 2020)

Correction to: Binomial nomenclature for virus species: a consultation - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2020)
The article Binomial nomenclature for virus species: a consultation, written by Stuart G. Siddell, Peter J. Walker, Elliot J. Lefkowitz, Arcady R. Mushegian, Bas E. Dutilh.

Binomial nomenclature for virus species: a consultation - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2020)
The Executive Committee of the International Committee on Taxonomy of Viruses (ICTV) recognizes the need for a standardized nomenclature for virus species. This article sets out the case for establishing a binomial nomenclature and presents the advantages and disadvantages of different naming formats. The Executive Committee understands that adopting a binomial system would have major practical consequences, and invites comments from the virology community before making any decisions to change the existing nomenclature. The Executive Committee will take account of these comments in deciding whether to approve a standardized binomial system at its next meeting in October 2020. Note that this system would relate only to the formal names of virus species and not to the names of viruses.

Changes to virus taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2019) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Donald M. Dempsey; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; R. Curtis Hendrickson; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Additional changes to taxonomy ratified in a special vote by the International Committee on Taxonomy of Viruses (October 2018) - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Michael J. Adams; Bas E. Dutilh; Alexander E. Gorbalenya; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; et al. (Archives of Virology, 2019)

Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2018) - Andrew M. Q. King; Elliot J. Lefkowitz; Arcady R. Mushegian; Michael J. Adams; Bas E. Dutilh; Alexander E. Gorbalenya; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; et al. (Archives of Virology, 2018)

Virus classification – where do you draw the line? - Peter Simmonds; Pakorn Aiewsakun (Archives of Virology, 2018)

Genomic analysis of a novel picornavirus from a migratory waterfowl, greater white-fronted goose (Anser albifrons) - Ákos Boros; Péter Pankovics; Peter Simmonds; Tamás Kiss; Tung Gia Phan; Eric Delwart; Gábor Reuter (Archives of Virology, 2018)

Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2017) - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

50 years of the International Committee on Taxonomy of Viruses: progress and prospects - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max L. Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2016) - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2016)

A splice acceptor site mutation in TaGW2-A1 increases thousand grain weight in tetraploid and hexaploid wheat through wider and longer grains - James Simmonds; Peter Scott; Jemima Brinton; Teresa C. Mestre; Max Bush; Alicia del Blanco; Jorge Dubcovsky; Cristobal Uauy (Theoretical and Applied Genetics, 2016)

Brain viral burden, neuroinflammation and neurodegeneration in HAART-treated HIV positive injecting drug users - Donald B. Smith; Peter Simmonds; Jeanne E. Bell (Journal of NeuroVirology, 2014)

Rosavirus: the prototype of a proposed new genus of the Picornaviridae family - Tung Gia Phan; Nguyen Phung Vo; Peter Simmonds; Erik Samayoa; Samia Naccache; Charles Y. Chiu; Eric Delwart (Virus Genes, 2013)

Recombination in the evolution of human rhinovirus genomes - Chloe L. McIntyre; Carita Savolainen-Kopra; Tapani Hovi; Peter Simmonds (Archives of Virology, 2013)

Determination and analysis of complete coding sequence regions of new discovered human bocavirus types 2 and 3 - Thaweesak Chieochansin; Peter Simmonds; Yong Poovorawan (Archives of Virology, 2010)

Allelic Variation of HERV-K(HML-2) Endogenous Retroviral Elements in Human Populations - Catriona Macfarlane; Peter Simmonds (Journal of Molecular Evolution, 2004)

Familial breast cancer: an investigation into the outcome of treatment for early stage disease - Diana Eccles; Peter Simmonds; Jonathan Goddard; Marie Coultas; Shirley Hodgson; Fiona Lalloo; Gareth Evans; Neva Haites (Familial Cancer, 2001)

Influence of Some Fatty Acids on Oviposition by the Bruchid Beetle, Callosobruchus maculatus - Martin J. Parr; Bruno M. D. Tran; Monique S. J. Simmonds; Geoffrey C. Kite; Peter F. Credland (Journal of Chemical Ecology, 1998)